Polymeric one-side conductive Janus separator with preferably oriented pores for enhancing lithium metal battery safety - Xu, Lulu (2022)
Recently, lithium metal batteries (LMBs) have regained significant attention as a type of promising rechargeable energy storage device with desired high energy density and long lifetime. Nevertheless, the persistent growth of lithium dendrites during the lithium dripping/stripping process could induce severe safety issues and shorten the lifespan of LMBs, limiting their practical application. In this work, we designed a polymeric one-side conductive Janus separator with preferably oriented pores to effectively reduce the local current density of the electrode and thus minimize the active sites for the germination of lithium dendrites, while also simultaneously enhancing the ionic conductivity to stabilize the Li anode. Such Janus separators could be facilely fabricated from polyvinyl alcohol (PVA) and polyaniline (PANI) precursor aqueous solutions via directional freezing and phase inversion. Our characterization results show that the Janus separator exhibits good surface electrical conductivity on its PANI side and much enhanced ion conductivity owing to the preferably oriented pores and high porosity and also displays a good balance of flexibility and stiffness, excellent wrinkle resistance, and high thermal stability. Moreover, it is confirmed that the Janus separator with oriented pores can efficiently retard the growth of lithium dendrites and promote the formation of a uniform and stable solid electrolyte interphase layer. As a result, compared with the reference separators, including a PVA-PANI Janus separator with random pores, the Janus separator with preferably oriented pores provides cells with a stable and long cycling lifespan and a much higher coulombic efficiency. This work provides a promising new approach to safe, stable and high-performance rechargeable LMBs.